The Concept Of Green Economy As a Challenge and Development Guideline of Gorski Kotar - Kovačić, Mirjana; Perić Hadžić, Ana; Kerčević, Srđan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The passage of time brings a pronounced trend of population decline but also prolongation of life span. The share of the third age population is increasing, and the gap between the rich and the poor is growing. There is also the problem of rural areas lagging urban areas and depopulation, which is not only a problem of the hilly and mountainous region of Gorski Kotar (GK) but is also present in the most developed countries of the European Union (EU). The current socio-economic model is not sustainable in the long term and innovative / different solutions are needed. One of these solutions is the application of the green economy (GE) concept, which links the stimulation of economic growth and job creation with increased care for environmental protection and equality, efficient use of resources and social inclusion. The paper explains the basic determinants, principles, and goals of the GE, as well as the most important challenges in the field of energy transition and establishing a circular economy. The authors analyze needs and potential in the field of sustainable environmental management in GK. Thematic areas were identified as key development challenges. The authors explain the advantages of green construction and emphasize the importance of regional connectivity and mobility. The presentation of the research results is summarized in the SWOT analysis.